United Arab Emirates : 2017 Article IV Consultation- Press Release; Staff Report and Informational Annex for the United Arab Emirates. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the economic performance of the United Arab Emirates was subdued during most of 2016. Together with weaker oil prices and slower oil output growth, the postponement of some public infrastructure projects and a slowdown in global trade caused growth to moderate to 3 percent from 3.8 percent in 2015. Economic activity is expected to strengthen gradually in the coming years with firming oil prices and other global indicators, and an easing pace of fiscal consolidation. Non-oil growth is projected to rise to 3.3 percent in 2017 from 2.7 percent in 2016, reflecting increased domestic public investment and a pickup in global trade.